The Influence of Field Trips and Reading Interest on Writing Skills - Pasaribu, Dwi Maulidayanti; Ramadhan, Syahrul (Jurnal Onoma: Pendidikan, Bahasa, dan Sastra, 2025)
This study aimed to examine the influence of the field trip learning method and reading interest on junior high school students’ ability to write observational report texts. The research was motivated by the importance of writing skills as part of 21st-century literacy, as well as the need for instructional strategies that are contextual and responsive to learners’ characteristics. A quasi-experimental method with a 2x2 factorial design was employed, involving two seventh-grade classes. The experimental class was taught using the field trip method, while the control class followed conventional instruction. Reading interest was measured through a validated and reliable questionnaire and categorized into two levels: high and low. The primary instrument for assessing writing skills was a test on observational report texts, evaluated based on six indicators: relevance of content and title, structure, paragraph cohesion, sentence effectiveness, diction, and accuracy of spelling and mechanics. Data were analyzed using normality tests, homogeneity tests, t-tests, and two-way ANOVA with SPSS 27. The findings revealed that there was no significant overall difference between the experimental and control groups; however, significant differences were observed among students with both high and low reading interest who participated in the field trip method. In addition, a significant interaction was found between learning method and reading interest in influencing writing skills. These results indicate that the effectiveness of instructional methods is strongly influenced by students’ internal factors, such as reading interest. Therefore, it is recommended that teachers implement contextual and differentiated learning strategies, taking into account students’ characteristics and needs in order to optimize writing learning outcomes.